2020
DOI: 10.3390/microorganisms8040602
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungal Assemblages Significantly Shifted upon Bacterial Inoculation in Non-Contaminated and Petroleum-Contaminated Environments

Abstract: Arbuscular mycorrhizal fungi (AMF) have been shown to reduce plant stress and improve their health and growth, making them important components of the plant-root associated microbiome, especially in stressful conditions such as petroleum hydrocarbons (PHs) contaminated environments. Purposely manipulating the root-associated AMF assemblages in order to improve plant health and modulate their interaction with the rhizosphere microbes could lead to increased agricultural crop yields and phytoremediation performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 75 publications
0
15
1
Order By: Relevance
“…Sampling was conducted in artificial sedimentation basins of a former petrochemical plant located in Varennes, Montreal region, Quebec, Canada (45 • 41 56 N 73 • 25 43 W), where petroleum hydrocarbon wastes were dumped for several decades. Details on the site of study were previously published [18,29,30]. An exhaustive vegetation inventory [31] was conducted in one of the decantation basins sampled in the present experiment, where the authors described the site as being patchy revegetation dominated by Eleocharis obtusa and Panicum capillare.…”
Section: Site Of Study and Samplingmentioning
confidence: 99%
“…Sampling was conducted in artificial sedimentation basins of a former petrochemical plant located in Varennes, Montreal region, Quebec, Canada (45 • 41 56 N 73 • 25 43 W), where petroleum hydrocarbon wastes were dumped for several decades. Details on the site of study were previously published [18,29,30]. An exhaustive vegetation inventory [31] was conducted in one of the decantation basins sampled in the present experiment, where the authors described the site as being patchy revegetation dominated by Eleocharis obtusa and Panicum capillare.…”
Section: Site Of Study and Samplingmentioning
confidence: 99%
“…It is believed that the distinctive microbiome around aromatic plants is highly specific and dependant on the plant species and on the related nature and abundance of secondary metabolites, present in the root exudates (Köberl et al, 2013;Adamovic et al, 2015;Misra et al, 2019). Apart from the effects of plant's driven changes on microbial communities, it has been previously reported that mycorrhizal inoculation can also influence the microbial community structure (Lioussanne et al, 2010;Akyol et al, 2019;Monokrousos et al, 2019;Dagher et al, 2020a). Soil bacteria may obtain carbon from AMF hyphae exudates or use the hyphae themselves as substrate (Qin et al, 2016;Gui et al, 2017), creating a niche for the growth of specific bacteria (Toljander et al, 2006;Gui et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well-described in the literature that, although the impact of vegetation on soil microbial communities depends on both the growing season and the plant species [ 10 , 17 , 39 ], fungal diversity usually decreases in the rhizospheric soil, in comparison with the bulk (loosely associated with the roots) or unplanted soil [ 75 ]. This fact is notably attributable to the selective pressure exerted by plant root exudates on the fungal communities; even more so in the vicinity of the root, the rhizosphere [ 17 , 38 , 39 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting results have been published. Some reports indicate a clear shaping of the microbial communities in response to AMF inoculation [ 9 , 10 , 32 , 33 , 34 ]; however, some others have demonstrated no influence of inoculation on the native fungal or AMF communities in the rhizosphere [ 35 , 36 ]. For instance, it was described that inoculating with Glomus sp.…”
Section: Introductionmentioning
confidence: 99%